The condition of the rural hospitality enterprises in rural tourism: the case of Serbia - Vujko, Aleksandra (2018)
Rural attractions has increasing opportunities to act as a basic resource for tourism, organised and sustained through locally owned small enterprises. Rural hospitality enterprises (RHEs) are a rapidly expanding and dynamic sector of the rural tourism industry, largely associated with the concept of sustainability in which local communities are increasingly proactive in facilitating the regional development. The research was aimed to determine the real condition of the accommodation capacity in rural tourism of Serbia. The authors employed a questionnaire to obtain data on the RHEs in thirteen (13) municipalities in Serbia. Thanks to the obtained results, the current condition of RHEs and potentials for more prosperous rural tourism development in the researched municipalities, can clearly be noticed.